2020
DOI: 10.18415/ijmmu.v7i7.1701
|View full text |Cite
|
Sign up to set email alerts
|

Problematics of Implementation of Inclusion Education in the Elementary School of Bengkulu City

Abstract: This study was aimed at investigating the implementation, obstacles, and solution to inclusive education at the primary school level in Bengkulu City. This study used a qualitative approach with the analysis of the Miles and Huberman flow model. Data was collected through observation, in-depth interview and study document. The findings of the study were; firstly, most of schools have not implemented inclusive education during the teaching and learning activities yet. Secondly, four obstacles in implementing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…In regular schools the implementation of learning is generally managed according to national education standards (SNP) Furthermore, according to (Dewi et al, 2020) in the research on inclusive schools in Bengkulu City, the conclusions are 1) a lack of available human resources and a lack of understanding of teachers about inclusive schools, 2) there is still minimal learning design and learning tools for students with special needs, 3) lack of direction from the local government regarding the technical implementation of inclusive schools, 4) there is no working group (POKJA) and guidance from other parties. Meanwhile, according to (Sasongko and Sahono, 2013) that only 4% of elementary schools in Bengkulu Province have fulfilled the SNP, so the low achievement of the SNP indicates that the standard processes carried out in inclusive schools in Bengkulu City have also not been achieved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In regular schools the implementation of learning is generally managed according to national education standards (SNP) Furthermore, according to (Dewi et al, 2020) in the research on inclusive schools in Bengkulu City, the conclusions are 1) a lack of available human resources and a lack of understanding of teachers about inclusive schools, 2) there is still minimal learning design and learning tools for students with special needs, 3) lack of direction from the local government regarding the technical implementation of inclusive schools, 4) there is no working group (POKJA) and guidance from other parties. Meanwhile, according to (Sasongko and Sahono, 2013) that only 4% of elementary schools in Bengkulu Province have fulfilled the SNP, so the low achievement of the SNP indicates that the standard processes carried out in inclusive schools in Bengkulu City have also not been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, according to (Sasongko and Sahono, 2013) that only 4% of elementary schools in Bengkulu Province have fulfilled the SNP, so the low achievement of the SNP indicates that the standard processes carried out in inclusive schools in Bengkulu City have also not been achieved. (Dewi et al, 2020) reported that based on data from Kementerian Pendidikan dan Kebudayaan Riset dan Teknologi of Bengkulu Province, in Bengkulu City, there are 15 Inclusive Schools at the Elementary School level, and of the 15 schools whose accreditation has received superior scores are 5 schools while the rest are still very good and some are still of good value.…”
Section: Introductionmentioning
confidence: 99%